2019
DOI: 10.1186/s41240-019-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

Total replacement of dietary fish oil with alternative lipid sources in a practical diet for mandarin fish, Siniperca scherzeri, juveniles

Abstract: A 12-week feeding trial was designed to evaluate the effect of total replacement of fish oil (FO) with terrestrial alternative oils on growth, feed utilization, body composition, hematological parameters, and fillet fatty acid profile of mandarin fish juveniles. Four iso-nitrogenous (56% crude protein) and iso-lipidic (13% crude lipid) practical diets were formulated. A control diet contained 6% FO and three other experimental diets were prepared by replacing FO with linseed oil, soybean oil, and lard (designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…Attempts have been made to search another fads2 gene from S. chuatsi genome data, but these have so far been unsuccessful. Although the S. chuatsi seems more like a marine fish without LC-PUFA biosynthesis ability, a feeding trial demonstrated that total replacement of dietary FOs with alternative VO has no negative impact on the growth performance and health of mandarin fish juvenile, which indirectly suggested this species could bioconvert C18 PUFA to their corresponding LC-PUFA (Sankian et al, 2019). Collectively, these findings highlight that teleosts have an adaptive plasticity and diversity of LC-PUFA biosynthesis mechanism (Fonseca-Madrigal et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Attempts have been made to search another fads2 gene from S. chuatsi genome data, but these have so far been unsuccessful. Although the S. chuatsi seems more like a marine fish without LC-PUFA biosynthesis ability, a feeding trial demonstrated that total replacement of dietary FOs with alternative VO has no negative impact on the growth performance and health of mandarin fish juvenile, which indirectly suggested this species could bioconvert C18 PUFA to their corresponding LC-PUFA (Sankian et al, 2019). Collectively, these findings highlight that teleosts have an adaptive plasticity and diversity of LC-PUFA biosynthesis mechanism (Fonseca-Madrigal et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Although these data of genes conversion rates in the present study are somewhat different from those in the previous studies; the order of genes conversion rates in grouper, rabbitfish, salmon, and eel is consistent in the present study and previous works. Consistently, nutritional trials have shown that VO can satisfy the essential fatty acid (EFA) requirements of Ctenopharyngodon idellus, Siganus canaliculatus, Anguilla japonica, S. chuatsi, and Salmo salar; and their 6 fad gene expression was increased by dietary VO (rich in C18 PUFA) (Takeuchi et al, 1980;Monroig et al, 2011;Lei et al, 2017;Xie et al, 2018;Sankian et al, 2019), whereas E. coioides 6 Fad had a low enzymatic activity in converting LNA and LA because of the deficiency of binding site for the stimulatory protein 1 (Sp1) in its promoter (Li et al, 2014;Xie et al, 2018). Among the freshwater species, herbivorous C. idellus has a higher 6 Fad activity than has carnivorous S. chuatsi, and the similar effect of feeding habit on the desaturase's activity was also exhibited between the marine species.…”
Section: Discussionmentioning
confidence: 88%
“…Dietary inclusion of dried housefly ( Musca domestica ) pupa [25] and defatted yellow mealworm ( Tenebrio molitor ) [26] has been shown to increase disease resistance against pathogenic Edwardsiella tarda in red seabream ( Pagrus major ). Yellow mealworm is also known to increase the enzyme activities of the immune systems of European seabass ( Dicentrarchus labrax ) [27], rainbow trout [28], mandarin fish ( Siniperca scherzeri ) [29], and pearl gentian grouper ( Epinephelus lanceolatus × Epinephelus fuscoguttatus ) [30]. Our previous studies showed that bioactive polysaccharides from the melon fly ( Bactrocera cucurbitae ) [5], Japanese oak silkmoth ( Antheraea yamamai ) [6], and silkmoth ( Bombyx mori ) [7] successfully prevent bacterial diseases via the activation of innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the alternatives, lipids of plant origin have been shown to be suitable replacers for dietary fish oil (Sankian et al, 2019; Yıldız et al, 2020). However, vegetable oils (VOs) are devoid of highly unsaturated fatty acid (HUFA), which influence reproductive success and the subsequent developmental stages (Arslan et al, 2016; Fernández‐Palacios et al, 2011; Salze et al, 2005).…”
Section: Introductionmentioning
confidence: 99%